2006
DOI: 10.1080/09540260600583072
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive lipids in schizophrenia

Abstract: SummaryBioactive lipids, in particular arachidonic acid (AA), are vital for monoaminergic neurotransmission, brain development and synaptic plasticity. Phospholipases A2 (PLA2) are key-enzymes in AA metabolism and are activated during monoaminergic neurotransmission. Reduced membrane AA levels, and an altered activity of PLA2 have been found in peripheral membranes of drug-naïve patients with schizophrenia with some conflicting results in more chronic patient populations. Furthermore, in vivo brain phosphorus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 136 publications
(144 reference statements)
0
52
0
8
Order By: Relevance
“…Decreased omega-3 fatty acid levels have been found in blood and postmortem brain cell membranes in several neuropsychiatric conditions (Schachter et al, 2005), in particular schizophrenia (Berger et al, 2006;Fenton et al, 2000;McNamara et al, 2007), bipolar affective disorders (Chiu et al, 2003;Hitzemann et al, 1984;Mahadik et al, 1996;Ranjekar et al, 2003), major depression (FrasureSmith et al, 2004;McNamara et al, 2006;Mischoulon and Fava, 2000;Peet et al, 1998), and attention deficit (hyperactivity) disorder (Burgess et al, 2000;Stevens et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased omega-3 fatty acid levels have been found in blood and postmortem brain cell membranes in several neuropsychiatric conditions (Schachter et al, 2005), in particular schizophrenia (Berger et al, 2006;Fenton et al, 2000;McNamara et al, 2007), bipolar affective disorders (Chiu et al, 2003;Hitzemann et al, 1984;Mahadik et al, 1996;Ranjekar et al, 2003), major depression (FrasureSmith et al, 2004;McNamara et al, 2006;Mischoulon and Fava, 2000;Peet et al, 1998), and attention deficit (hyperactivity) disorder (Burgess et al, 2000;Stevens et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Also, these oxidative modifications are not disease specific but occur in a number of neurodegenerative diseases. Recent theories on the neurological deficits of schizophrenia have focused on abnormalities in phospholipid metabolism, particularly increased activity of PLA 2 enzymes and reduced activity of the system which incorporates PUFAs into phospholipids (a simultaneous increase in phospholipid hydrolysis and decrease in synthesis) [57,58]. Neither abnormality alone produces schizophrenia but the presence of both does [57].…”
Section: Als and Lipid Peroxidationmentioning
confidence: 99%
“…Also, since phospholipid metabolism has a crucial role in neuronal and synaptic growth and remodeling, it is plausible that defects in this system result in failure of normal neurodevelopment in schizophrenia. There is also evidence that schizophrenia is associated with alterations in lipid transport proteins and membrane phospholipid composition (increase in phosphatidylserine and decrease in phosphatidylcholine and phosphatidylethanolamine) [58]. Genome studies have found that several genes involved in myelination have decreased expression levels in schizophrenia [59].…”
Section: Als and Lipid Peroxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain's LCPUFAs are involved in the maturation of neuronal structures and are essential throughout the entire lifespan for maintaining normal brain activities (5,6). Consequently, it is unsurprising that a lack of n-3 LCPUFAs or an imbalance in the n-3 and n-6 ratio has been associated with a number of neurological and psychiatric disorders, including depression, anxiety, schizophrenia, and attention deficit hyperactivity disorder in both children and adults (7)(8)(9)(10)(11)(12).…”
Section: Diet Compositionmentioning
confidence: 99%